Telomerase Expression Increased the Risk of Borderline Ovarian Tumors - Mila Maidarti (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objective: To compare the expression of telomerase in benign ovarian tumors and borderline ovarian tumors. Methods: Thirteen samples of paraffin blocks of ovarian borderline tumors and benign ovarian tumors were taken from patients who underwent surgery from January 2006 to December 2011. In all samples, we performed immunohistochemical staining to the paraffin blocks. Semi quantitative determination of the expression of telomerase is done by an Anatomic Pathology specialist and Gynecologist, which already had the same perception about assessing the standardization sample. We used Fisher’s test to analyze the data. Results: There were significant relationship in the moderate expression of telomerase in the nucleus and cytoplasm between benign and borderline ovarian tumors, with an odds ratio of moderate telomerase expression in the cytoplasm and nucleus of 19.3 (95% CI: 1.4 - 943) and 26 (95% CI : 2.3 - 1211). This means that the risk of borderline ovarian tumors in the expression of moderate telomerase in the cytoplasm was 3.19 times compared to the negative expression, whereas in the nucleus it became 26-fold. There is no significant relationship among menopause, age, and telomerase expression in the nucleus and cytoplasm. Conclusion: There are significant differences in the expression of moderate strength telomerase in nucleus and cytoplasm between benign and borderline ovarian tumors. [Indones J Obstet Gynecol 2013; 37-1: 32-40] Keywords: benign ovarian tumor, borderline ovarian tumor, telomerase expression